2022
DOI: 10.1007/s00432-022-04445-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation status of the SPHK1 and LTB genes underlies the clinicopathological diversity of non-alcoholic steatohepatitis-related hepatocellular carcinomas

Abstract: Purpose This study was performed to identify the DNA methylation profiles underlying the clinicopathological diversity of non-alcoholic steatohepatitis (NASH)-related hepatocellular carcinomas (HCCs).  Methods Genome-wide DNA methylation analysis of 88 liver tissue samples was performed using the Infinium assay. Results Principal component analysis revealed that distinct DNA methylation profiles differing from such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Many studies have confirmed DNA methylation changed in liver biopsy of patients with NAFLD 45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] (Figure 3). A recent investigation revealed a marked reduction in global DNA methylation among 47 individuals diagnosed with NAFLD compared to a cohort of 18 lean subjects without NAFLD, as assessed via liver biopsy.…”
Section: Clinical Researchmentioning
confidence: 95%
See 2 more Smart Citations
“…Many studies have confirmed DNA methylation changed in liver biopsy of patients with NAFLD 45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] (Figure 3). A recent investigation revealed a marked reduction in global DNA methylation among 47 individuals diagnosed with NAFLD compared to a cohort of 18 lean subjects without NAFLD, as assessed via liver biopsy.…”
Section: Clinical Researchmentioning
confidence: 95%
“…112 Inappropriate binding of DNA methyltransferase to unrepaired damage or mismatches may promote local histone deacetylation, methylation, and regional hypermethylation, leading to tumour suppressor gene silencing. 64,98,113 The low FA may lead to a compensatory increase of MTHFR. HCC cancer patients with higher MTHFR had a worse survival rate.…”
Section: Appropriate Folic Acid May Prevent Tumour Formation and Prog...mentioning
confidence: 99%
See 1 more Smart Citation
“…Infinium data for 25 NASH-Ns, 25 NASH-Ts, 37 V-Ns, 37 V-Ts, and 36 NLTs were also included in our previous papers focusing on NASH-related hepatocarcinogenesis: 29 U-Ns, 29 U-Ts, 16 AL-Ns, and 16 AL-Ts (90 samples in total) were originally examined for this study. [13][14][15][16]…”
Section: Infinium Assaymentioning
confidence: 99%
“…DNA hypomethylation resulting in increased expression of the SPHK1 and LTB genes in poorly differentiated HCCs may underlie the aggressive phenotype of such HCCs. 15 Moreover, we have identified tumor-related genes, such as WHSC1, 13 TRIM4, PRC1, and TUBA1B, 16 whose expression levels are regulated by DNA methylation status, as potential therapeutic targets in NASH-related HCCs.…”
Section: Introductionmentioning
confidence: 99%